Profitability and marketing behavior of cauliflower crop in Sonipat district of Haryana - KUMAR, AJAY; ROHILA, ANIL KUMAR (The Indian Journal of Agricultural Sciences, 2018)
India is the second largest producer of vegetables in the world next to China. The cauliflower, potato, onion, tomato and radish are the major vegetable crops of Haryana. The present investigation was carried out to study the cost structure, returns, resource use efficiency, price spread and marketing efficiency of cauliflower. Present study was conducted in Sonipat district of Haryana. From selected district one tehsil and two villages from tehsil were selected on the basis of highest area and 15 farmers from each selected village were interviewed. Thus, sample of30 cauliflower growers were studied. The vegetable markets of   Sonipat district was purposively selected as these  are near to the main production area. While, Sonipat and Panipat markets were selected for the marketing efficiency. Ten intermediaries from each market were selected randomly making a sample of 20 intermediaries. The cost of cultivation of cauliflower was higher on large farms as compared to medium and small farms.The gross returns were found higher in medium farms as compared to large and small farms. The cost of production per quintal was lower onmedium farms and highest on large and small farms indicating that the medium farms are having economies of scale in production. The net income was higher on medium farms as compared to small and large farms in cauliflower.There was no difference in marketable and marketed surplus because of perishable nature of vegetable and farmers were hard pressed by their cash needs for post-harvest immediate sale. In cauliflower channel-I (Producer → Commission agent cum wholesaler →Retailer →Consumer) was more efficient as it ensured higher percent share of farmer in the consumer's rupee as compared to channel-II (Producer → Village trader → Commission agent cum wholesaler→Retailer →Consumer).